Different iPSC-derived neural stem cells shows various spectrums of spontaneous differentiation during long term cultivation - Galiakberova, Adelya Albertovna; Brovkina, Olga Igorevna; Kondratyev, Nikolay Vitalyevich; Artyuhov, Alexander Sergeevich; Momotyuk, Ekaterina Dmitrievna; Kulmukhametova, Olga Nikolaevna; Lagunin, Alexey Aleksandrovich; Shilov, Boris Vladimirovich; Zadorozhny, Anton Dmitrievich; Zakharov, Igor Sergeevitch; Okorokova, Larisa Sergeevna; Golimbet, Vera Evgenievna; et al. (Frontiers in Molecular Neuroscience, 2023)
Culturing of human neural stem cells (NSCs) derived from induced pluripotent stem cells (iPSC) is a promising area of research, as these cells have the potential to treat a wide range of neurological, neurodegenerative and psychiatric diseases. However, the development of optimal protocols for the production and long-term culturing of NSCs remains a challenge. One of the most important aspects of this problem is to determine the stability of NSCs during long-term in vitro passaging. To address this problem, our study was aimed at investigating the spontaneous differentiation profile in different iPSC-derived human NSCs cultures during long-term cultivation using immunocytochemistry, qPCR, bulk transcriptomes and scRNA-seq. Our results indicate a significant dependence of the spectrum of differentiated cells on both the number of passages and the original iPSC lineage, suggesting that both internal (genetic and epigenetic) and external (conditions and duration of cultivation) factors influence the stability of NSCs. These results have important implications for the development of optimal NSCs culturing protocols and highlight the need to further investigate the factors influencing the stability of these cells in vitro.